The Need to Study Political Psychology in Malaysia (Journal of Science, Technology and Innovation Policy, 2023)
This paper aims to describe political psychology and its significance in the context of Malaysian politics. Political studies in Malaysia primarily rely on political science, political sociology, and socio-political analysis. However, it is crucial to examine the political environment and issues in Malaysia from a psychological perspective. Political psychology provides insights into the thinking and behaviour of political leaders and enables an understanding of voters' behaviour. This interdisciplinary approach enriches our comprehension of politics from diverse angles. In the Malaysian context, studying political psychology will enhance our understanding of numerous variables related to political practices. The interaction between politics and psychology, particularly the impact of psychology on politics, is an intriguing subject to explore. A deeper comprehension of political psychology in Malaysia will enable leaders to better appreciate the aspirations of the people and work towards fulfilling their needs. The study of political psychology should aim to uncover the thought processes of political actors and voters alike.
Keywords: Political psychology, Malaysian Politics, Political Leadership, Political Behaviour